Nitric Oxide in Fungi: Production and Function - Nan-Nan Yu; Gyungsoon Park (Journal of Fungi, 2024)
Nitric oxide (NO) is synthesized in all kingdoms of life, where it plays a role in the regulation of various physiological and developmental processes. In terms of endogenous NO biology, fungi have been less well researched than mammals, plants, and bacteria. In this review, we summarize and discuss the studies to date on intracellular NO biosynthesis and function in fungi. Two mechanisms for NO biosynthesis, NO synthase (NOS)-mediated arginine oxidation and nitrate- and nitrite-reductase-mediated nitrite reduction, are the most frequently reported. Furthermore, we summarize the multifaceted functions of NO in fungi as well as its role as a signaling molecule in fungal growth regulation, development, abiotic stress, virulence regulation, and metabolism. Finally, we present potential directions for future research on fungal NO biology.